1966
DOI: 10.1002/cber.19660990835
|View full text |Cite
|
Sign up to set email alerts
|

Aromatische Phosphine mit Substituenten zweiter Ordnung, III. Eine neue Variante der Wittig‐Reaktion

Abstract: Phosphoniumsalze aus p-Diphenylphosphino-benzoesaure eignen sich fur die Wittig-Reaktion. Hierbei entsteht p-Diphenylphosphinyl-benzoesaure (7a), die leichter als Triphenylphosphinoxid von der Olefinkomponente abgetrennt werden kann. e Phosphoniumsalze (C6H5)3P -CHR1R2]X0 geben in Gegenwart starker Basen mit Carbonylverbindungen Olefine und Triphenylphosphinoxid (Wittig-Reaktion)J). Bei solchen Olefinen, die durch funktionelle Gruppen relativ stark polar sind, konnen Schwierigkeiten bei der Trennung der Reakti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…3-(4 ‘ -Dimethylaminophenyl)-( E )-propenoic acid methyl ester (17). 17 was obtained from a Wittig reaction between 4-dimethylaminobenzaldehyde (1.0 mmol, 149 mg) and (methoxycarbonylmethylene)triphenylphosphorane (1.5 mmol, 502 mg) in water (5.0 mL) at 90 °C for 2 h. The crude product was purified using flash chromatography (10% EtOAc/hexane, R f 0.40) to give 81% (166 mg) of 17 as a yellow solid; mp 132−135 °C ( E/Z -ratio: 90/10) {lit . mp 134−135 °C}: 1 H NMR (500 MHz, CDCl 3 ) δ 7.63 (d, C H β CH α , J = 15.9 Hz, 1H), 7.41 (m, aromatic, 2H), 6.66 (m, aromatic, 2H), 6.22 (d, CH β C H α , J = 15.9 Hz, 1H), 3.77 (s, OC H 3 , 3H), 3.01 (s, (CH 3 ) 2 N, 6H); 13 C NMR (125 MHz, CDCl 3 ) δ 168.3, 151.8, 145.4, 129.8, 122.3, 112.2, 111.9, 51.4, 40.1; FTIR (CH 2 Cl 2 , cm -1 ) 1701, 1600, 1265, 735.…”
Section: Methodsmentioning
confidence: 99%
“…3-(4 ‘ -Dimethylaminophenyl)-( E )-propenoic acid methyl ester (17). 17 was obtained from a Wittig reaction between 4-dimethylaminobenzaldehyde (1.0 mmol, 149 mg) and (methoxycarbonylmethylene)triphenylphosphorane (1.5 mmol, 502 mg) in water (5.0 mL) at 90 °C for 2 h. The crude product was purified using flash chromatography (10% EtOAc/hexane, R f 0.40) to give 81% (166 mg) of 17 as a yellow solid; mp 132−135 °C ( E/Z -ratio: 90/10) {lit . mp 134−135 °C}: 1 H NMR (500 MHz, CDCl 3 ) δ 7.63 (d, C H β CH α , J = 15.9 Hz, 1H), 7.41 (m, aromatic, 2H), 6.66 (m, aromatic, 2H), 6.22 (d, CH β C H α , J = 15.9 Hz, 1H), 3.77 (s, OC H 3 , 3H), 3.01 (s, (CH 3 ) 2 N, 6H); 13 C NMR (125 MHz, CDCl 3 ) δ 168.3, 151.8, 145.4, 129.8, 122.3, 112.2, 111.9, 51.4, 40.1; FTIR (CH 2 Cl 2 , cm -1 ) 1701, 1600, 1265, 735.…”
Section: Methodsmentioning
confidence: 99%
“…The 13C NMR spectra of 2 (see Figure 1) and its proton NMR spectra revealed that two, chemically nonequivalent isopropyl groups had been introduced. 6 The presence of a nonacylated NH group in the structure of 2 was indicated by its proton NMR spectra in pyridine-ds and dry methyl-dg sulfoxide solutions, each of which displayed a broad, one-proton signal at low field that was displaced to higher field on addition of deuterium oxide to the solution. The chemical shift of this signal was found to be highly variable, in agreement with its assignment as an NH proton.…”
Section: Resultsmentioning
confidence: 99%
“…In the preparation of 2,2-dialkoxyoxetanes via thermal cycloadditions, instability of the desired product under the reaction conditions has to be considered when hydrogen atoms are present on C3. McElvain isolated5 the ,/3-unsaturated ester (10) from the reaction between 1,1 -diethoxyethene (6) and hexanal (7) at 150 °C, and ascribed the result to elimination of ethanol from an initially formed oxetane (8), followed by ring opening of the second intermediate (9). We found that 6 reacts at room temperature with more electron- poor carbonyl compounds (chloral, benzoyl cyanide, p-chlorobenzaldehyde).…”
mentioning
confidence: 92%
“…mp: 173–177 °C (lit:21 161–163 °C). 1 H NMR (CDCl 3, δ): 7.86 (d, J = 15.5 Hz, 2H, CHAr), 7.66 (s, 4H, phenylene CH), 6.75 (d, J = 15.5 Hz, 2H, CHCO).…”
Section: Methodsmentioning
confidence: 99%